Pemikiran Pendidikan KH. Hasyim Asy'ari dalam Kitab Adab Al'alim Wa Al-Muta'alim - Mislawaty, Sri Eva; Febriyanti, Febriyanti (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the educational thought of KH. Hasyim Asy'ari as presented in the book Adab Al-‘Ālim wa Al-Muta‘allim. This type of research is a literature review, which involves examining and analyzing various scholarly sources such as books, journals, and relevant articles. The data collection tool consists of written documents relevant to the research topic. The data analysis technique used is content analysis, which involves reviewing the content, meaning, and relevance of literature sources to systematically and critically formulate conclusions. Based on the results and discussion, the book Adab al-‘Ālim wa al-Muta‘allim by KH. Hasyim Asy’ari emphasizes that adab (ethics and manners) is the main foundation in Islamic education to attain the blessings of knowledge. The book elaborates in detail the ethics of both teachers and students, emphasizing that mastery of knowledge must be accompanied by noble character. Teachers are expected to be role models in patience, sincerity, and moral responsibility, while students must have sincere intentions, respect their teachers, and be diligent in learning. By referring to classical scholars' thoughts, the book remains relevant across generations, stressing the importance of education that touches the intellect, heart, and moral values holistically